2015
DOI: 10.3892/or.2015.4183
|View full text |Cite
|
Sign up to set email alerts
|

RRM1, TUBB3, TOP2A, CYP19A1, CYP2D6: Difference between mRNA and protein expression in predicting prognosis of breast cancer patients

Abstract: Abstract. The study investigated the clinical significance of RRM1 (ribonucleoside reductase subunit M1), TUBB3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…TUBB3 is mainly expressed in the nucleus, and immunohistochemistry showing brown granules indicates positive expression (18). Research has confirmed the correlation between TUBB3 expression and the chemosensitivity of taxanes, and TUBB3 has been confirmed as a prognostic predictor of various solid tumors such as breast, ovarian, prostate and lung cancer (6). In the present study, the DFS and OS of human breast cancer patients with TUBB3-or TOP2A-positive tumors were lower than the DFS and OR of the patients with TUBB3-or TOP2A-negative tumors.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…TUBB3 is mainly expressed in the nucleus, and immunohistochemistry showing brown granules indicates positive expression (18). Research has confirmed the correlation between TUBB3 expression and the chemosensitivity of taxanes, and TUBB3 has been confirmed as a prognostic predictor of various solid tumors such as breast, ovarian, prostate and lung cancer (6). In the present study, the DFS and OS of human breast cancer patients with TUBB3-or TOP2A-positive tumors were lower than the DFS and OR of the patients with TUBB3-or TOP2A-negative tumors.…”
Section: Discussionsupporting
confidence: 74%
“…tissues is also related to the sensitivity of chemotherapeutic agents (6). Research has shown that TUBB3 expression is closely related to drug resistance of taxanes.…”
Section: Suppression Of Pten/akt Signaling Decreases the Expression Omentioning
confidence: 99%
See 1 more Smart Citation
“…Study had demonstrated that TOP2A identified and provided epigenetic rationale for novel combination therapeutic strategies for aggressive prostate cancer [26] . Moreover, we could find the prognostic value of TOP2A in nasopharyngeal carcinoma and breast cancer [27] , [28] . Ubiquitin-conjugating enzyme E2 C ( UBE2C ), a member of the E2 ubiquitin-conjugating enzyme family, was required for the destruction of mitotic cyclins and for cell cycle progression and may be involved in cancer progression.…”
Section: Discussionmentioning
confidence: 96%
“…DNA topoisomerase 2-alpha (TOP2A) gene encodes a protein that controls and alters topologic states of DNA during the process of transcription. TOP2A is a signi cant prognostic factor in predicting the breast cancer patients' OS, and low expression of TOP2A has been associated with a better clinical outcome [49]. In addition TOP2A ampli cation or deletion is also known to enhance responsiveness to anthracycline-containing chemotherapy regimens relative to non-anthracycline regimens [50].…”
Section: Discussionmentioning
confidence: 99%